Instrumental Activities of Daily Living and Quality of Life Among Older Adults with Hypertension: A Cross-Sectional Study in Grogol, Indonesia - Syifa Aulia; Agus Sudaryanto (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Global population aging is accelerating, including in Indonesia, and is accompanied by an increasing burden of chronic conditions such as hypertension. Older adults with hypertension are vulnerable to functional decline, particularly in instrumental activities of daily living (IADL), which may adversely affect their quality of life (QoL). However, empirical evidence examining the relationship between IADL and QoL in primary healthcare settings remains limited. Objective: This study aimed to examine the association between instrumental activities of daily living and quality of life among older adults with hypertension attending a primary health center. Methods: A cross-sectional study was conducted involving 382 older adults with hypertension registered at the Grogol Health Center. IADL was assessed using the Lawton Instrumental Activities of Daily Living scale, while QoL was measured using the Kualitas Kehidupan Lansia (KKHL) questionnaire. Descriptive statistics were presented as medians and interquartile ranges (IQRs) due to non-normal data distribution. The association between IADL and QoL was analyzed using Spearman’s rank correlation test. Results: The median QoL score was 56 (IQR: 50–58), indicating relatively homogeneous quality of life among participants. Most respondents demonstrated functional independence in IADL. A statistically significant but weak positive correlation was found between IADL and QoL (ρ = 0.131; p = 0.010; 95% CI: 0.03–0.23). Conclusion: Functional independence in IADL was positively associated with QoL among older adults with hypertension, although the strength of the relationship was weak. Other contributing factors should be explored to better understand determinants of QoL in this population.